Atherosclerosis and inflammation: Current therapeutic strategies. A review - Marina Yu. Zubareva; Igor V. Sergienko (ZAO "Consilium Medicum", 2024)
Atherosclerosis is a chronic condition that is the main underlying cause of cardiovascular disease. Inflammation is one of the key factors in the pathogenesis of atherosclerosis and its complications. This review explains an up-to-date understanding of the immunological mechanisms of atherogenesis and biomarkers of inflammation, as well as available treatments for low-intensity chronic inflammation. Information is provided on the perspective directions of anti-inflammatory therapy for atherosclerosis being studied.